Problems of Integrative Thematic Learning in Elementary Schools - Vhila, Indri; Gustina, Gustina; Zulhendri, Zulhendri (Journal of Islamic Education Students (JIES), 2022)
This study aims to describe the problems of integrative thematic learning faced by teachers in planning, implementing, and evaluating integrative thematic learning. This research is included in qualitative research due to the method used by researchers through descriptive methods. Data obtained through observation, interviews, personal documentation and other official documentation. The results obtained from this study are that integrative thematic learning in elementary schools has not run optimally. This can be seen from some of the problems encountered, among others, problems in terms of planning where there are some teachers who are not yet able to operate electronic and computer media so that in making learning tools including lesson plans they still need the help of other teachers and in the implementation of learning, teachers still tend to get confused explains learning that is integrated or connected to several subjects in one theme. The teacher's lack of understanding about integrative thematic learning, the teacher has not prepared interesting learning media and the lack of learning resources used.